Agronomic comparison among cucumber (Cucumis sativus) types - Cruz-Coronado, Jose Aníbal (2020)
Introduction:  Cucumber is an important vegetable crop in Costa Rica.  Objective:  The objective of the study was to evaluate yield and quality of three cucumber types (long, medium, and small) grown under greenhouse and hydroponic conditions at the Agricultural Experimental Station Fabio Baudrit Moreno located in Alajuela, Costa Rica.  Methods:  The crop was planted on coconut fiber as substrate, pruned to one stem per plant, and managed with fertigation.  Results:  The harvest of small cucumber type started 26 days after transplant (dat), and for medium and long type cucumbers it started between 28 and 30 dat.  Data show a wide variability between cucumber types with respect to:  fruit length (11,89 – 31,74 cm), diameter (43,15 – 50,37 mm) and weight (143,07 – 488,19 g); number of fruits (22,81 – 90,14) and yield per plant (8656,32 – 12911,67 g); yield per area ( 22,48 – 33,54 kg/m2); and percentage of total soluble solids (3,03 – 3,22 °Brix).  The highest total number of fruits per plant (90,14) resulted from small cucumber type, while the lowest number of fruits per plant (22,81) and the fruits with the highest fruit weight (488,19 g) were obtained with long cucumber type.  The total (33,54 kg/m2), commercial (27,10 kg/m2) and first quality yield (16,41 kg/m2) were significantly higher with small cucumber type.  Conclusions:  Small cucumber type is considered the most recommended under the conditions tested from an economical point of view, although the consumer preference in Costa Rica for this cucumber type remains to be evaluated.